Cutaneous and Labyrinthine Tolerance of Bioactive Glass S53P4 in Mastoid and Epitympanic Obliteration Surgery: Prospective Clinical Study. (4th October 2015) - Bernardeschi, Daniele; Nguyen, Yann; Russo, Francesca Yoshie; Mosnier, Isabelle; Ferrary, Evelyne; Sterkers, Olivier
Abstract : Objective . To evaluate the cutaneous and the inner ear tolerance of bioactive glass S53P4 when used in the mastoid and epitympanic obliteration for chronic otitis surgery. Material and Methods . Forty-one cases have been included in this prospective study. Cutaneous tolerance was clinically evaluated 1 week, 1 month, and 3 months after surgery with a physical examination of the retroauricular and external auditory canal (EAC) skin and the presence of otalgia; the inner ear tolerance was assessed by bone-conduction hearing threshold 1 day after surgery and by the presence of vertigo or imbalance. Results . All surgeries but 1 were uneventful: all patients maintained the preoperative bone-conduction hearing threshold except for one case in which the round window membrane was opened during the dissection of the cholesteatoma in the hypotympanum and this led to a dead ear. No dizziness or vertigo was reported. Three months after surgery, healing was achieved in all cases with a healthy painless skin. No cases of revision surgery for removal of the granules occurred in this study. Conclusion . The bioactive glass S53P4 is a well-tolerated biomaterial for primary or revision chronic otitis surgery, as shown by the local skin reaction which lasted less than 3 months and by the absence of labyrinthine complications.